The EU's strategic autonomy in times of politicisation of international trade: The future of commission accountability - Wolfgang Weiß (Global Policy, 2023)
Trade relations face unprecedented challenges, which has led to an increased politicisation and contestation of trade rules. In response, the EU has changed its trade policy under the motto `Open Strategic Autonomy' towards a more assertive policy. The EU seeks to significantly expand its room of manoeuvre and to gain more autonomy by strengthening the enforcement of its trade rights and by ensuring more effectively, including unilaterally, a level playing field. This reorientation engenders several new or amended trade policy instruments, but meets with reservations as the renewed politicisation of EU trade policy will have internal consequences and raise demands for more democratic accountability of the European Commission. The new policy instruments will enlarge its leeway in trade policy. The future of the EU's multilateral, rule- instead of power-oriented political stance becomes unclear, which might undermine its negotiation position in WTO reform and collide with the EU's respect for international law. The tensions of the EU's new hybrid approach with its international commitments even more fuel demands for increased accountability of the Commission as a safeguard against employing the new powers for protectionism and disrespect to international law. The contribution analyses the need for increased Commission accountability in the redirected trade policy.
Keywords: 320